Who Wears the Pants? Gender Identity Norms and Intrahousehold Financial Decision‐Making - KE, DA (Journal of Finance, 2021)
ABSTRACT Using microdata from U.S. household surveys, I document that families with a financially sophisticated husband are more likely to participate in the stock market than those with a wife of equal financial sophistication. This pattern is best explained by gender identity norms, which constrain women's influence over intrahousehold financial decision‐making. A randomized controlled experiment reveals that female identity hinders idea contribution by the wife. These findings underscore the roles of intrahousehold bargaining and traditional norms in shaping household financial decisions.